HUBUNGAN DENTAL FLUOROSIS DENGAN KANDUNGAN FLUOR PADA AIR SUMUR DI KECAMATAN RATATOTOK KABUPATEN MINAHASA TENGGARA - Mariati, Ni Wayan (Jurnal Biomedik : JBM, 2010)
Abstract: Dental fluorosis occurs due to the excessive intake of fluoride from fluoride in the water supply, naturally occurring or having been added to it, or from other sources. The damages in tooth development caused by the overexposure of fluoride occur between the ages of 6 months to 5 years. Teeth are generally composed of hydroxyapatite and carbonated hydroxyapatite. When fluoride is present, fluorapatite is created. Excessive fluoride can cause yellowing of the teeth, white spots, and pitting or mottling of enamel. The aim of this study was to analyze the correlation between fluoride contents in the well water and dental fluorosis in the Ratatotok District, South East Minahasa. This research was conducted in the Ratatotok District, South East Minahasa and Clinical Laboratory of North Sulawesi Province Health Office from November 2008 until February 2009. This was an analytically explorative research using 50 respondents and the well water used. This research showed that 1) the majority of the respondents who had dental fluorosis were 13-14 years old, 2) the majority of the respondents who had dental fluorosis were female, 3) the fluoride contents of the well water tested was normal, and, 4) the fluoride contents had correlations with dental fluorosis. From the results, we concluded that fluoride contents in the well water had correlations with dental fluorosis occurring in the students of junior and senior high schools in the Ratatotok District, South-East Minahasa region. Keywords: Ratatotok, fluor content, well water, dental fluorosis Â  Abstrak: Dental fluorosis terjadi karena asupan yang berlebihan dari fluor yang terdapat pada sumber air, yang ada secara alami atau sebagai hasil penambahan fluor atau melalui sumber-sumber lainnya. Kerusakan perkembangan gigi terjadi pada umur antara 6 bulan sampai 5 tahun melalui paparan berlebihan fluor. Gigi biasanya terdiri dari hydroxyapatite dan carbonated hydroxyapatite, saat fluor ada, fluoropatite terbentuk. Fluor yang berlebihan dapat menyebabkan gigi berwarna kuning, titik putih dan berlubang atau berwarna. Penelitian ini bertujuan untuk menganalisis hubungan kandungan fluor pada air sumur dengan dental fluorosis di Kecamatan Ratatotok Kabupaten Minahasa Tenggara. Penelitian ini telah dilak-sanakan di Kecamatan Ratatotok Kabupaten Minahasa Tenggara dan Laboratorium Klinis Dinas Kesehatan Provinsi Sulawesi Utara pada bulan November 2008 sampai Maret 2009. Penelitian ini merupakan penelitian analitik eksploratif terhadap 50 responden dan air sumur yang mereka gunakan. Hasil penelitian menunjukkan bahwa 1) sebagian besar responden dental flurosis (DF) terdistribusi pada kelompok umur 13-14 tahun, 2) sebagian penderita dental fluorosis ialah perempuan, 3) pada umumnya kandungan fluor (F) masih berada pada kategori normal dan 4) kandungan fluor pada air sumur berhubungan dengan dental fluorosis Dari penelitian ini, dapat disimpulkan bahwa kandungan fluor pada sumber minum berhubungan dengan dental fluorosis di Kecamatan Ratatotok Kabupaten Minahasa Tenggara. Kata Kunci: Ratatotok, kandungan fluor, air sumur, dental fluorosis